2014
DOI: 10.1007/s10695-014-9925-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and quantitative detection of GABAA receptor in Carassius auratus gibelio

Abstract: Gamma-aminobutyric acid (GABA), a major inhibitory neurotransmitter in brain, is synthesized from glutamate and metabolized to succinic semialdehyde by glutamic acid decarboxylase (GAD) and GABA transaminase (GABA-T), respectively. The fast inhibitory effect of GABA is mediated by GABA type A (GABAA) receptors that are associated with several neurological disorders, and GABAA receptors are targets of several therapeutic agents. To date, information on the distribution and quantity of GABAA receptors in Carassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The studies of Ruan et al. (, ) also found that the residual AVM in the liver and kidneys were reduced successively under the conditions of 24 h LC 50 (0.127 mg L −1 ), 48 h LC 50 (0.071 mg L −1 ), and 96 h LC 50 (0.039 mg L −1 ). One report revealed that AVM can affect the function of a cytochrome P450 enzyme system and oxidation stress, which cause tissue morphology, and induce apoptosis by expression of caspase‐3, caspase‐8, and fas mRNA in the liver and kidneys of king pigeons (Zhu, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The studies of Ruan et al. (, ) also found that the residual AVM in the liver and kidneys were reduced successively under the conditions of 24 h LC 50 (0.127 mg L −1 ), 48 h LC 50 (0.071 mg L −1 ), and 96 h LC 50 (0.039 mg L −1 ). One report revealed that AVM can affect the function of a cytochrome P450 enzyme system and oxidation stress, which cause tissue morphology, and induce apoptosis by expression of caspase‐3, caspase‐8, and fas mRNA in the liver and kidneys of king pigeons (Zhu, ).…”
Section: Discussionmentioning
confidence: 86%
“…These processes attenuate sensitivity to excitatory or inhibitory signal transfer reactions in insects, affect normal neural activities, and eventually cause paralysis and death (Wang, ). While the effects of AVM on small animals such as mice (Soderlund et al., ; Krflgek and Zemkovfi, ), rats (Abalis et al., ), guinea pigs (Coccini et al., ), finfish (Deng et al., ; Lumaret et al., ), and mammals (Robertson, ) and the distribution of GABA A R in C. gibelio have been studied (Ruan et al., ), the effects of AVM on C. gibelio remain unknown. Therefore, this paper investigated the effects of different medium lethal concentrations of AVM on the protein expression of GABA A R in C. gibelio by Western blot and immunohistochemistry methods.…”
Section: Introductionmentioning
confidence: 99%
“…GABA mediates the release of inhibitory synapses of neurons, which can reduce the hyperexcitability of neurons. Previous study found that crucian carp suffered from impatience and restlessness, body type Fish Physiol Biochem (2020) 46:1965-1973 tremors when treated with DIF (Ruan et al 2014a). Meanwhile, it was also found in this paper that GAD 65 , GAD 67 , and GABA-T levels were significantly downregulated at 0.083 and 12 h in the brain after administrated with DIF at its SD (20 mg/kg b. W.), while GAD 65 , GAD 67 , and GABA-T levels were significantly upregulated at LD 50 (2840 mg/kg b. W.) of DIF (P < 0.01, Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports suggested FQs could have caused severe neurotoxic reactions, which lead to hallucinations, depression, and other neurological diseases (Barrett and Login 2009;Grill and Maganti 2011;Guiol et al 1993). It had been reported that norfloxacin (Xi et al 2019) and DIF (Ruan et al 2014a) caused non-target biological neurotoxicity. Albino male mice treated with ciprofloxacin were found the levels of Glu and GABA significantly reduced (Arafa et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanisms for these effects are neurophysiological disturbances, in particular, a different ion flow across the GABA-A receptors (Nilsson et al, 2012;Heuer and Grosell, 2014). GABA-A receptors are ubiquitous in the brain and can also be found in the retina and tectum, two main structures of the visual systems of fish (Lin and Yazulla, 1994;Anzelius et al, 1995b;Anzelius et al, 1995a;Pirone et al, 2006;Ruan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%